Impact of Multiple Sclerosis on Foot Health and Quality of Life: A Prospective Case-Control - Sánchez-Ruiz, Francisco Javier; Martins, Maria do Rosário; Losa-Iglesias, Marta Elena; Becerro-de-Bengoa-Vallejo, Ricardo; Gómez-Salgado, Juan; Romero-Morales, Carlos; Jiménez-Cebrián, Ana María; López-López, Daniel (Frontiers, 2023)
Objectives: To assess quality of life or factors related to the foot and general health and to determine the impact taking into account foot health status in people with multiple sclerosis (MS). Methods: 50 subjects with MS and 50 healthy subjects were studied using the Foot Health Status Questionnaire, that is a validated and is reliable tool was used to assess foot health and quality of life. This instrument comprise four domains for evaluate the foot health (foot function, foot pain, footwear and general foot health) in the first section and for measure the general health comprise four domains (general health, physical activity, social capacity and vigor) for second section and was use for all participants. Results: In both groups of the sample, 50% (n = 15) were men and 50% (n = 35) women, and the mean age in the case group was 48.04 ± 10.49 and the control group was 48.04 ± 10.45 were recruited. A statistically significant difference (p < 0.05) was shown for foot function, general foot health, general health, physical activity and vigor domains, stating that people with MS have a lower related to foot health (lower FHSQ scores) compared to healthy subjects who have higher FHSQ scores. There were no statistically significant differences (p > 0.05) for the scores of the other domains of the FHSQ (foot pain, footwear and social capacity). Conclusion: Patients with MS suffer a negative impact on the quality of life related to foot health, which appears to be associated with the chronic disease.
Keywords: Pies - Cuidados de enfermería; Esclerosis múltiple; Quality of life; Foot care; Multiple sclerosis; Foot health; Foot health status questionnaire